(3QSGdI JhHjN dGMbs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HGSec Gddge Edi GdWdjb GdNGFH GdfGcK GdYGb GdYGLR Yf MejO GdWGYI Edi GdYUjGf hGdEHGb s
(3BNQgG (B:s
(3hMSHi KbJi HbGFe GdOjf hUGMH GdGeQ hGdfgi hGdefY hGdEWdGb Ke GdJhHjN hGdMeO dehdGfG hMOg hGdTcQ dbGFe GdReGf YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3abg GdePGgH GdCNQis